2020
DOI: 10.1136/annrheumdis-2020-219099
|View full text |Cite
|
Sign up to set email alerts
|

Non-surgical and surgical treatments for rotator cuff disease: a pragmatic randomised clinical trial with 2-year follow-up after initial rehabilitation

Abstract: BackgroundRotator cuff disease (RCD) causes prolonged shoulder pain and disability in adults. RCD is a continuum ranging from tendinopathy to full-thickness tendon tear. Recent studies have shown that subacromial decompression and non-surgical treatments provide equivalent results in RCD without a full-thickness tendon lesion. However, the importance of surgery for full-thickness tendon tears remains unclear.MethodsIn a pragmatic, randomised, controlled trial, 417 patients with subacromial pain underwent 3-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Along these lines, it is worth noting that recent knowledge indicates a short-term effect of interventions including surgery for subacromial impingement when used as part of a second-line treatment approach. 5 In the study by Cederqvist et al, 5 patients were first prescribed a 3- to 4-month physical therapist−led exercise intervention, and patients who failed this approach were randomized to either continuation of the previously initiated rehabilitation program or a surgical intervention. At 3 months after randomization, between-group differences in improvements were in favor of the surgery group, with differences of 10 to 15 points on the VAS.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, it is worth noting that recent knowledge indicates a short-term effect of interventions including surgery for subacromial impingement when used as part of a second-line treatment approach. 5 In the study by Cederqvist et al, 5 patients were first prescribed a 3- to 4-month physical therapist−led exercise intervention, and patients who failed this approach were randomized to either continuation of the previously initiated rehabilitation program or a surgical intervention. At 3 months after randomization, between-group differences in improvements were in favor of the surgery group, with differences of 10 to 15 points on the VAS.…”
Section: Discussionmentioning
confidence: 99%
“…Longer follow-up and the results of ongoing studies are needed to evaluate the optimal treatment for trauma-related rotator cuff tears. 34 In the latest randomized trial comparing nonsurgical and surgical treatments for rotator cuff disease, Cederqvist et al 4 reported that surgery yielded superior improvement in pain and function in patients with full-thickness rotator cuff tears at 2-year follow-up. This study also included larger rotator cuff tears comprising not only the supraspinatus tendon.…”
Section: Discussionmentioning
confidence: 99%
“…1 Our randomised, pragmatic, controlled trial compared surgical and non-surgical treatments for rotator cuff disease (RCD) with or without full-thickness tendon tears after unsuccessful initial rehabilitation. 2 Randelli and coworkers commented that the power of our study lies in the fact that potential eligible patients underwent a systematic, adequately performed 3-month rehabilitation, after which only patients who remained symptomatic were randomised; we agree. Symptoms alleviated in 102 of the 417 shoulders with chronic RCD (mean duration of symptoms 9 months before recruitment) during the 3 month, pragmatic nonoperative treatment.…”
mentioning
confidence: 61%